Recent Insights Into Electronic Performance, Magnetism and Exchange Splittings in the Cr-substituted CaO - Doumi, Bendouma; Mokaddem, Allel; Tadjer, Abdelkader; Sayede, Adlane (Frontiers in Chemistry, 2020)
The first-principles computations of density functional theory are employed to characterize the structural properties, electronic structures and ferromagnetism induced by Cr impurities in Ca1-xCrxO compounds at concentrations x = 0.25, 0.5 and 0.75. The dynamic stability is performed by the phonon spectra calculations. The structural parameters are computed by using Wu-Cohen generalized gradient approximation, while the electronic and magnetic properties are determined by the accurate Tran-Blaha-modified Becke-Johnson exchange potential. The crystal field, direct and indirect exchange splittings were investigated to determine the origin and stability of ferromagnetic state configuration. The Ca1-xCrxO systems have right half-metallicities, which are verified by the spin polarization of 100 % and the integer values of total magnetic moments. The Ca0.75Cr0.25O, Ca0.5Cr0.5O and Ca0.25Cr0.75O are half-metallic ferromagnetic with flip-gaps of 1.495, 0.888 and 0.218 eV, respectively. Therefore, the Ca1-xCrxO materials are suitable candidates for possible applications of spin-injection in future semiconductors spintronics.